Multi-Criteria Decision Analysis Using TOPSIS Method for Scholarship Recipients Selection: A Comprehensive Implementation Study - Fauziyah Fauziyah; Dwi Lestari; Minik Rinayanti; Iskandar Zulkarnain (Universitas Muria Kudus, 2025)
This study implemented the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to select scholarship recipients from eight candidates studied. The selection process considers four main relevant criteria, namely Cumulative Achievement Index (GPA), Parental Income, Non-Academic Achievement, and Number of Family Dependents.Â The weights for each criterion were 0.35 for GPA (benefit), 0.25 for Parental Income (cost), 0.20 for Non-Academic Achievement (benefit), and 0.20 for Number of Family Dependents (cost). The TOPSIS method is applied through several stages, starting from the normalization of the decision matrix and weighting, to the determination of positive and negative ideal solutions and the calculation of distance to obtain the relative proximity value. The results showed that the candidates with the highest relative proximity scores were the most recommended to receive the scholarship. The study provides a systematic and transparent framework in scholarship selection decision-making, which can help ensure fair and effective scholarship allocation.